Automatic Gas Detection System (AGD System) - Mohd Alıas, Muhammad Arıf Akmal; Mahat, Aishah; Md Takıyudın, Muhammad Alıff Syafıq Bın; Ahmad Kamal, Alı Imran (2020)
As we can see from social media and news, there are many accidents happened due to Liquefied Petroleum Gas. There are also too many loses from these accidents in term of damages, injuries, and even death. Thus, a system that prevent these dangerous gases from leaking has been innovated in order to improve the safely of people and environment. This system is called Automatic Gas Detection Equipment System (AGD System) that functions to alert by producing a sound and a red light to warn if there is any leakage of dangerous gases. It also notified the owner through their smartphone by sending a push notification. This system can detect these gases and prevent from any critical accidents from happening. Besides, this system used lowers power and easy to use. The main targets are those people in a residential area, restaurant, laboratory and factory. AGD system should be commercialized because it can bring a lot of benefits in general.